Volumetric zirconia stabilization using carbon nanotubes - Faglioni, Felipe D. [UNESP]; Pereira, Cristian G.B. [UNESP]; Estrada, Flávia R.; Neto, Vicente Gerlin; Foschini, Cesar R. [UNESP] (Elsevier, 2025)
Carbon-based materials (CBMs) have been considered promising reinforcing agents in ceramic composites. This study investigates the potential of carbon nanotubes (CNTs) as stabilizers for the tetragonal phase of yttria-stabilized-zirconia (YSZ). The CNT-YSZ composites were produced by conventional sintering techniques in a carbon-rich-atmosphere. We observed a significant reduction in the yttria content required for stabilization due to carbon diffusion into the zirconia crystalline lattice. High-resolution synchrotron X-ray diffraction and Rietveld refinement analyses confirmed the YSZ phase transformation from monoclinic to tetragonal, as well as lattice extensive strain. These findings suggest that CNTs, and potentially other CBMs, can effectively stabilize zirconia phases under conventional sintering, thus representing a cost-effective and environmentally-friendly alternative. The successful implementation of these results using conventional industrial sintering techniques underscores the practical feasibility of this approach, paving the way for advanced ceramic composites with enhanced mechanical properties and reduced environmental impact.